Hučivá Cave: a Magdalenian hunting camp in the Tatra Mountains. (August 2022) - Valde-Nowak, Paweł; Baca, Mateusz; Cieśla, Magda; Kościuk-Załupka, Julia; Kraszewska, Anna; Lemanik, Anna; Nadachowski, Adam; Popović, Danijela; Skłucki, Jakub; Sojak, Marian
Abstract: Abstract : This article discusses the objectives of the Stone Age Man in Caves of the Tatra Mountains project, which aims to explain the mysterious absence of evidence for the Palaeolithic in the Tatra Mountains of Eastern Europe. We present preliminary work from Hučivá Cave, which demonstrates clear traces of Magdalenian settlement within this region.